Collaborative Governance in Financing Street Vendors in the Aur Kuning Market Area - Agung Ramadhan; Adil Mubarak (Journal of Management and Social Sciences, 2026)
Although research on Collaborative Governance in public program implementation has been widely studied, research examining collaboration between local governments and Islamic financial institutions in financing Street Vendors (PKL) remains limited. This study aims to analyze and describe Collaborative Governance between the Bukittinggi City Government and PT. BPRS Jam Gadang in implementing the Utsman Program for financing Street Vendors in the Aur Kuning Market Area, as well as identifying factors influencing its implementation. This study used a qualitative case study approach. Informants were selected through purposive sampling, involving representatives of the Bukittinggi City Government, PT. BPRS Jam Gadang, and Utsman Program beneficiaries. Data were collected through interviews, observations, and documentation, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that Collaborative Governance in the Utsman Program is implemented through cross-sector collaboration with clear role distribution, communication, coordination, and shared commitment between institutions. Supporting factors include regulatory support, effective communication, institutional commitment, and financial resources. However, administrative complexity, limited socialization, and challenges in achieving business independence remain obstacles. The study concludes that effective Collaborative Governance requires strong inter-organizational relationships and sustainable financial support to strengthen empowerment programs for Street Vendors.